Unbalance compensation topology for railway application based on pulse width modulation alternating current chopper - Ismail Mir; Anas Benslimane; Jamal Bouchnaif; Badreddine Lahfaoui (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
This paper focuses the study on the design of a new topology of unbalance compensators adopted by railway operators in the substations of high-speed railway lines, this compensation structure based on the concept of alternating current (AC)-chopper controlled impedance (CCI). The present document describes the CCI compensator in terms of the components constituting this structure, the installation of CCI to limit the unbalance factor according to the limit imposed by the moroccan energy provider (ONEE), and the calculation of the power losses generated by the CCI and the comparison with other topologies such as voltage source inverter STATCOM (VSI) and current source inverter STATCOM (CSI). The modelization of the compensator and the results were established using MATLAB/Simulink software by exploiting real data provided by the moroccan railway office (ONCF).